Novel bismuth compounds: synthesis, characterization and biological activity against human adenocarcinoma cells. Issue 35 (21st March 2016) - Arda, M.; Ozturk, I. I.; Banti, C. N.; Kourkoumelis, N.; Manoli, M.; Tasiopoulos, A. J.; Hadjikakou, S. K.
Abstract : Novel bismuth(iii ) halide compounds were synthesized. Molecules with lower H-all atoms inter-molecular interactions tend to exhibit the higher activity against MCF-7 and HeLa cells. Abstract : Five new bismuth(iii ) halide compounds (BiX3, X = Br or I) of formulae [BiBr(Me2 DTC)2 ] n (1 ), [BiBr2 (Et2 DTC)] n (2 ), [BiI2 (Me2 DTC)] n (3 ), [BiI(Et2 DTC)2 ] n (4 ) and [BiI(μ2 -I)(Et2 DTC)2 ]2 n (5 ) (Me2 DTCH = dimethyldithiocarbamate, C3 H7 NS2 and Et2 DTCH = diethyldithiocarbamate, C5 H11 NS2 ) were synthesized from the reactions between bismuth(iii ) bromide (BiBr3 ) or bismuth(iii ) iodide (BiI3 ) with tetramethylthiuram monosulfide (Me4 tms), tetramethylthiuram disulfide (Me4 tds) or tetraethylthiuram disulfide (Et4 tds). The complexes were characterized by melting point, elemental analysis, FT-IR spectroscopy, Raman spectroscopy, 1 H, 13 C NMR spectroscopy and Thermal Gravimetry-Differential Thermal Analysis (TG-DTA). Moreover, the crystal structures of1–5 were determined with single crystal X-ray diffraction analysis. The ligands of compounds1–5 were derived from reduction with concomitant degradation to dithiocarbamates. Complexes1–4 are polymers, whereas complex5 is a dimer, built up from monomeric units with square pyramidal (SP) geometry (1, 4 and5 ) and pentagonal bipyramidal geometry (2 and3 ) around the bismuth center. Complexes1–5 were evaluated for their in vitro cytotoxic activity against human adenocarcinoma breast (MCF-7) and cervix (HeLa) cells. The toxicity on normal human fetal lung fibroblast cells (MRC-5) is also evaluated. Since estrogen receptors (ERs) are located in MCF-7, in contrast to HeLa cells, the estrogenic effect of1–5 on MCF-7 cells was studied by means of a methylene blue assay. Hirshfeld surface volumes were analyzed to clarify the nature of the intermolecular interactions. Molecules with lower H-all atoms inter-molecular interactions tend to exhibit higher activity against both MCF-7 and HeLa cells. Structure–activity relationship (SAR) studies were performed for these complexes using 2D topological based disparity analysis. This finding underlines the significance of the halogen atoms in the coordination sphere of the metal ion.